Extended emission factors for future automotive propulsion in Germany considering fleet composition, new technologies and emissions from energy supplies. (15th July 2020) - Seum, Stefan; Ehrenberger, Simone; Pregger, Thomas
Abstract: Until today, road transport is largely fossil fuel driven and contributes significantly to greenhouse gas emissions and air pollutants. In order to assess the impact of development pathways of future transport, new emission factors for emerging technologies and a shift in the assessment framework that extends the emissions to include electricity generation is needed. The focus of this study is to provide emission factors for future passenger cars and fleets and offer an approach to comprehensively assess emission effects in future studies. Our scenario storyline approach imbeds different levels of changes in consideration of plausibility and consistency. We developed three pathways for Germany up to 2040 in order to capture the interdependencies of measures and developments. We hereby consistently modified the progress in transport technologies and in power generation together with changes in fleet compositions. Furthermore, we developed emission factors and energy consumption factors for plug-in hybrid and electric vehicles and expanded the conventional tank-to-wheel emission factors by including emissions derived from consistent energy scenarios. The development of emission factors depends on multiple factors, including vehicle and engine size. Furthermore, electrification shifts the emissions from tailpipe to power generation. Particularly for nitrogen oxides and particulate matter emissions, electric power generation for transport purposes could contribute significantly to ambient air emissions in the future, while tailpipe emissions can be expected to decline substantially. Highlights: Emission factors for future road traffic need to take energy supply into account. Technological changes in energy and transport needs to be analysed integratively New emission and consumption data are provided for plug-in hybrid and electric cars. Scenarios analysed for Germany in 2040 show significant quantitative differences. While tailpipe emissions decline power generation could remain significant.